The Influence of Professionalism, Organizational Culture, Internal Control, and Commitment on Employee Performance at Baki Health Center, Sukoharjo Regency - Supriyanto, Edy; Istiatin, Istiatin; Mursito, Bambang (Indonesian Journal of Islamic Economics and Finance, 2024)
This research aims to determine and explain the influence of professionalism, organizational culture, internal control, and commitment on employee performance at the Baki Community Health Center, Sukoharjo Regency. The population of this study was all 91 employees of the Baki Community Health Center, Sukoharjo Regency, using a saturated sampling technique. Data collection using questionnaires. The data analysis technique uses the Multiple Linear Analysis method. The research results show that professionalism, organizational culture, internal control, and organizational commitment positively and significantly affect performance. The variables Professionalism, Organizational Culture, Internal Control, and Organizational Commitment influence performance by 56.9%, while the remaining 43.1% is explained by other variables not proposed in this research. Suggestions from this research, employees of the Baki Community Health Center, Sukoharjo Regency can increase professionalism, organizational culture, and commitment to the organization with good internal supervision to achieve maximum performance results for the Baki Sukoharjo Community Health Center.